Lessons learned from The Spirit Catches You and You Fall Down: Student perspectives on how cultural differences can lead to health disparities. (February 2020) - Uy, Tricia; Dimaano, Christian
Objective: The Spirit Catches You and You Fall Down by Anne Fadiman is a critically acclaimed book describing the importance of understanding cultural influence on health care and health outcomes. Although this book has been incorporated into standard curriculum in the university and medical school training settings, consideration of how The Spirit Catches You and You Fall Down might change undergraduate student perceptions on health disparities, specifically among students at a minority-serving institution in the USA, has yet to be explored. Method: A qualitative, thematic analysis, using a pre-/post-test study design, assessed undergraduate students' perceptions of topics of health disparities, spirituality and trust in healthcare providers. A total of 43 student responses characterising their perceptions on these topics were used to define themes both before and after a course utilising Fadiman's book as a teaching tool. Results: Changes within the themes present in the post-test data showed that students had a deeper understanding of the need for communication with healthcare providers, as well as the need to build bridges between traditional spirituality and faith with modern medicine, in the context of respecting one's culture, to effectively promote health outcomes in a multicultural society. Conclusion: An undergraduate course with directed lesson plans taken from The Spirit Catches You and You Fall Down afforded undergraduate students at a US minority-serving institution with a way to contextualise why and how cultural differences can lead to health disparities.